Independent Collectors - Independent Collectors (2009)
[Dt.:] Kommerziell gesponsorte und geprägte Seite mit Informationen für private Kunstsammler, inkl. einer Sammlung von Videoaufnahmen bekannten Galeristen und Künstler. - [Engl.:] Commercially sponsored and informed site with information for private collectors, incl. an collection of video recordings of well-known gallerists and artists.